Proposed Strategy for Maintaining A Small-Family-Business Enterprise in a Competitive Property Market - Mayendra, Aliya (Syntax Literate, 2024)
This study addresses the growing challenges faced by small family businesses in the competitive property market by proposing strategic interventions specifically designed to sustain and enhance the viability of Allure Realty Group, a family-run enterprise established in 2012 in Jabodetabek. With increasing complexity in the property sector due to urbanization, shifting consumer demands, and stringent regulatory environments, the research aims to develop a robust strategic framework. The methodology involves a combination of qualitative and quantitative approaches, including surveys and interviews, to identify key problems and collect data. Analytical tools such as the Marketing Mix 7P, VRIO Framework, and STP Analysis for internal factors, and PESTLE Analysis, Porter’s Five Forces, Competitor and Customer Analysis for external factors are used to conduct SWOT and TOWS analyses for strategic development. The study hypothesizes that targeted strategies will significantly improve the business's resilience and competitiveness in the market. Key objectives include identifying challenges faced by Allure Realty Group, developing strategies to address these issues, and implementing actions to improve operational efficiency, customer satisfaction, and market expansion. The expected outcomes are enhanced operational frameworks, increased customer satisfaction, and a larger market share, contributing to the business's long-term sustainability. This research contributes to business management theory by providing insights into strategies for small family businesses in rapidly evolving markets. The findings aim to bridge traditional business values with modern management practices, offering valuable guidance for both academic researchers and business practitioners in navigating the complexities of the property industry.